The Impact of Federal Spending on House Election Outcomes - Levitt, Steven D.; Snyder,, James M. (Journal of Political Economy, 1997)
While it is widely believed by academics, politicians, and the popular press that incumbent members of Congress are rewarded by the electorate for bringing federal dollars to their district, the empirical evidence supporting that claim is extremely weak. One explanation for the failure to uncover the expected relationship between federal spending and election outcomes is that incumbents who expect to have difficulty being reelected are likely to exert greater effort in obtaining federal outlays. Since it is generally impossible to adequately measure this effort, the estimated impact of spending is biased downward because of an omitted variable bias. We address this estimation problem using instrumental variables. For each House district, we use spending outside the district but inside the state containing the district as an instrument for spending in the district. Federal spending is affected by a large number of actors (e.g., governors, senators, mayors, and other House members in the state delegation), leading to positive correlations in federal spending across the House districts within states. However, federal spending outside of a district is unlikely to be strongly correlated with the strength of that district's electoral challenge. In contrast to previous studies, we find strong evidence that federal spending benefits congressional incumbents: an additional $100 per capita in spending is worth as much as 2 percent of the popular vote. The only category of federal spending that does not appear to yield electoral rewards is direct transfers to individuals.